A new species of Ecitonides Wasmann, 1894 (Coleoptera: Staphylinidae: Paederinae) from Peru and phylogenetic placement of the genus based on molecular data - Shaw, Josh Jenkins; Rodríguez-Melgarejo, Maryzender; Matsumoto, Keita; Wasel, Sophia; Piper, Ross (Zootaxa, 2023)
Ecitonides constanceae sp. nov., a new species of the myrmecophilous genus Ecitonides Wasmann, 1894, which is associated with army ants (Hymenoptera: Formicidae: Ecitoninae), is described from Peru. The holotype, which is the only known specimen, was collected at light at Los Amigos Biological Station, Madre de Dios department, Peru. The army ant host species is unknown. The new species is distinguished from congeners and an updated key of the species, as well as a checklist of Ecitonides and their associated host ants are provided. Based on the holotype we non-destructively extracted DNA and sequenced two genes which were incorportated into an existing molecular phylogenetic dataset and analysed using Bayesian Inference. Ecitonides is recovered as sister to recently described thermitophilous genus Ruptor Żyła et al. 2022 and placed in the so-called ‘Medonina and allied taxa’ clade. Beyond Bayesian Inference phylogenetic analysis and their associated nodal support methods, we also explored the position of the Ecitonides within the posterior sample of trees produced in the Bayesian analyses, which further supported its placement.